Characteristics of Drinking Water Quality from Decentralized Units in Traghen: A Comparative Study with International and Local Standards - Abdulsalam Mohammed Aebeedat; Aml Mohamed Almurabit; Fatima Hosen Darkallh (African Journal of Advanced Pure and Applied Sciences, 2025)
This study aims to evaluate the performance of decentralized water treatment units in Traghen, Libya, by monitoring the quality of the produced water and comparing it with both national and international standards. A descriptive analytical approach was adopted, and six water samples were collected from three primary locations: the City Entrance, Student Housing, and the Grand Mosque (designated as C, B, and A, respectively). Three samples were taken from the water source before desalination, and three were collected after treatment from each site. Laboratory analyses included the measurement of key physicochemical parameters, such as pH, electrical conductivity (EC), and total dissolved solids (TDS). The concentrations of major ions, including sodium (Na+), potassium (K+), calcium (Ca++), magnesium (Mg++), chloride (Cl-), sulfate (SO₄²-), and bicarbonate (HCO₃-), were also determined. Additionally, nitrate (NO₃-) levels were measured. Statistical analysis was performed using the Statistical Package for the Social Sciences (SPSS), employing both an independent samples T-test and one-way analysis of variance (ANOVA) at a significance level of α=0.05. The results indicate that most of the physicochemical indicators for the treated water comply with national and international drinking water standards. The pH values ranged from 6.7 to 7.1, and all major ion concentrations were within the permissible limits. Nitrate concentrations across all samples were either very low or below the detection limit. However, a slight increase in the electrical conductivity and total dissolved solids was observed in some units after treatment, particularly at stations A and C. Furthermore, elevated concentrations of certain ions, such as sodium and chloride, were recorded at station C post-treatment. This suggests a variation in the efficiency of the desalination units and an incomplete removal of salts, a potential issue that could be attributed to manufacturing defects or a lack of proper maintenance and filter replacement